Construction Prototyping, Flight Dynamics Modeling, and Aerodynamic Analysis of Hybrid VTOL Unmanned Aircraft - Roman Czyba; Marcin Lemanowicz; Zbigniew Gorol; Tomasz Kudala (Journal of Advanced Transportation)
A challenging issue associated with fixed-wing Unmanned Aerial Vehicles (UAVs) is that these vehicles are often not appropriate for operating effectively in limited airspace. This problem emerges especially in urban environment where the usage of a runway is not possible, and UAVs usually have to fly at a relatively low speed and altitude. The development of a vertical take-off and landing (VTOL) fixed-wing plane is a promising trend which hopefully will solve this issue. This paper presents the design process of an unmanned vertical take-off and landing aircraft including prototyping of the airframe construction and mathematical modeling as well as computational fluid dynamics (CFD) simulations. The designed system is to be a hybrid platform, for which different operating modes correspond to the vertical flight, transition, and spatial flight in the airframe system. The paper discusses an iterative design process of the platform with emphasis on CAD design and aerodynamic analysis for particular flight modes. The operating prototype is presented and future plans for platform improvement are discussed.